Caracterização climática da mesorregião do Triângulo Mineiro/Alto Paranaíba e do entorno da Serra da Canastra (MG) - Novais, Giuliano Tostes (2011)
To characterize and define the meso-climate of the Triangulo Mineiro / Alto Paranaiba and also the surroundings of the Serra da Canasta, this work was divided into three chapters. Physical characterization of the study area was covered in Chapter 1, being divided into geology, geomorphology, vegetation and hydrography. Chapter 2 is divided into two items, population and economic activities. The climatic characterization of the region is discussed in Chapter 3, where the estimated temperature for all areas of the region together with the precipitation is analyzed by various weather maps. It was developed in this paper a detailed topographic map with the use of SRTM 15 images on a scale of 1:250,000, covering the entire region, and tens of distribution maps of climatic elements in the study area isotherms (temperature) and isohyetal (rainfall). At the end of the work is proposed a climatic classification for the study area, with a higher level of detail regarding the most used classifications in the country, expanding to the temperate climate region.